Desmoid tumour biology in patients with familial adenomatous polyposis coli - Schiessling, Serin; Kihm, Melanie Christine; Ganschow, Petra; Kadmon, Guni; Büchler, Markus W.; Kadmon, Martina (The British journal of surgery, 2013)
Familial adenomatous polyposis (FAP) is caused by mutations in the adenomatous polyposis coli (APC) gene. Desmoid tumours affect up to 26 per cent of patients and contribute significantly to death. This study aimed to assess the influence of sex and mutation site on desmoid tumour development and sex-specific genetic differences in patients with FAP with and without desmoid tumours.Patients with FAP-associated desmoid tumours recorded in the Heidelberg Polyposis Register between 1991 and 2010 were identified. These patients were analysed with respect to clinical parameters and possible risk factors.Some 105 patients with FAP-associated desmoid tumours of a total of 585 patients with FAP were analysed. Male patients had a significantly greater number of desmoid tumours and a larger tumour mass, although tumours were more common in female patients. Desmoid tumours in male patients were located more often in the abdominal wall. Seventy-nine (75·2 per cent) of the 105 patients demonstrated a clear temporal association between a previous operation and subsequent desmoid tumour development; most of these patients were female. Mutation sites in male patients were limited to exons 5, 14 and 15, whereas female patients carried mutations along the entire coding region of the APC gene. Twenty-one per cent of patients with desmoid tumours carried mutations within the ‘desmoid region’, compared with only 4·1 per cent of the control group without desmoids.There are significant sex differences concerning desmoid tumour manifestation. Female patients appear to have a higher risk of desmoid tumour occurrence independent of the mutation site, whereas in male patients the mutation site seems to exert more influence.
Gesehen am 24.06.2021